2014
DOI: 10.1073/pnas.1405216112
|View full text |Cite|
|
Sign up to set email alerts
|

Avian influenza H5N1 viral and bird migration networks in Asia

Abstract: The spatial spread of the highly pathogenic avian influenza virus H5N1 and its long-term persistence in Asia have resulted in avian influenza panzootics and enormous economic losses in the poultry sector. However, an understanding of the regional long-distance transmission and seasonal patterns of the virus is still lacking. In this study, we present a phylogeographic approach to reconstruct the viral migration network. We show that within each wild fowl migratory flyway, the timing of H5N1 outbreaks and viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
158
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 52 publications
3
158
0
1
Order By: Relevance
“…24 Recently, Tian and others showed that movement of the highly pathogenic avian influenza virus H5N1 is closely associated with known bird migration routes in Asia. 25 Thus, there is a very good evidence that migratory birds play an important role in the dissemination of the main tick vector of CCHFV and spread of H5N1. [21][22][23][24][25] Evidence that migratory birds may play a role in the distribution of CCHFV in Europe and spread of H5N1 in Asia point to the expectation that SFTSV will have a similarly wide range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Recently, Tian and others showed that movement of the highly pathogenic avian influenza virus H5N1 is closely associated with known bird migration routes in Asia. 25 Thus, there is a very good evidence that migratory birds play an important role in the dissemination of the main tick vector of CCHFV and spread of H5N1. [21][22][23][24][25] Evidence that migratory birds may play a role in the distribution of CCHFV in Europe and spread of H5N1 in Asia point to the expectation that SFTSV will have a similarly wide range.…”
Section: Discussionmentioning
confidence: 99%
“…25 Thus, there is a very good evidence that migratory birds play an important role in the dissemination of the main tick vector of CCHFV and spread of H5N1. [21][22][23][24][25] Evidence that migratory birds may play a role in the distribution of CCHFV in Europe and spread of H5N1 in Asia point to the expectation that SFTSV will have a similarly wide range. Adults, nymphs, and larvae of H. longicornis were found on Z. aurea, T. hortulorum, Halcyon coromanda, and P. nympha in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…rivers and lakes), whilst diverse poultry AIVs have been reported in Wuhan, no H7N9 has been documented to date (Su et al, 2015). In addition, both Zhejiang and Hubei represent habitats of the migratory birds that follow the east Asian-Australasian flyway (Tian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This could related to activity of wild birds migration and virus activity in low temperature seasons. In the study of 2015 in Asia were found that a closely association between bird migration networks in Asia and time of H5N1 outbreaks [14]. Furthermore, Asia and North Africa's low temperature in winter with cold and dry weather (especially January and February) increase poultry outbreaks and H5N1 transmission, this lead increase of human infection.…”
Section: Discussionmentioning
confidence: 98%